The Influence of Direction & Solid Loading Ratio on Two Phase Flow Energy - AbdulWahid, Ahmed Adeeb (Nahrain University College of Engineering Journal, 2010)
This research investigates the influence of solid loading ratio , Reynolds number & angle of flow direction change on minor losses coefficient for two-phase flow type gas-solid through an orifice by manufacturing a special apparatus with solving the equations mathematically . Three different angles of elbow 15 , 30 & 45 deg. was chosen to study this effect on minor losses head and minor losses coefficient for a solid loading ratio range 0 to 1.9 , Reynolds number range 36209 to 78078 . It is found that the minor losses head decrease with increase of mixture velocity and Reynolds number with relationship of elbow angle increasing linearly with solid loading ratio increment . also the minor losses coefficient increasing with minor losses head increment and linearly with mixture velocity , Reynolds number as same as solid loading ratio . fig.(1) shows the apparatus which used in this research .